THE ROLE OF JOB CRAFTING, WORK AUTONOMY, PSYCHOLOGICAL EMPOWERMENT IN ENHANCING INNOVATIVE WORK BEHAVIOR AMONG EMPLOYEES IN TECH STARTUP INDONESIA - Gloria Miagina Palako Djurubassa; Siti Waliah; Rr. Chusnu Syarifa Diah Kusuma; Rana Nadir Idrees; Pedro P. Raymunde JR (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
This research aims to analyse the role of job crafting, work autonomy, and psychological empowerment in increasing innovative work behaviour among technology startup employees in Indonesia. The research population includes employees working in various technology startup companies, with a sample of 200 respondents selected using purposive sampling techniques to ensure representation of individuals directly involved in innovation-based work processes. Data was collected through a structured questionnaire and analyzed using quantitative methods with a Structural Equation Modelling (SEM) approach to test the relationship between variables. The research results show that job crafting and psychological empowerment positively and significantly affect innovative work behaviour. This research also confirms that work autonomy does not significantly influence innovative work behaviour. These findings confirm that when employees can adapt their tasks, gain autonomy in decision making, and feel psychologically empowered, they are more likely to generate new ideas that support organizational growth. Theoretically, this research enriches the literature regarding the determinants of innovative work behaviour in the context of startups in Indonesia.